2022
DOI: 10.1155/2022/5507153
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Polymorphism of Matrix Metalloproteinase-9 and Susceptibility to Myocardial Infarction: A Meta-Analysis

Abstract: Objective. Current findings on the association between MMP-9 rs3918242 and susceptibility to myocardial infarction (MI) are inconsistent, and their definite relationship is discussed in this meta-analysis. Methods. Eligible literatures reporting MMP-9 rs3918242 and susceptibility to MI were searched in PubMed, Cochrane Library, CNRI, and VIP using keywords such as “MMP-9”, “matrix metallopeptidase-9” and “myocardial infarction”, “acute myocardial infarction”, “AMI”, and “polymorphism”. Data from eligible liter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 26 publications
0
9
0
Order By: Relevance
“…53 MMP9 levels were significantly elevated in patients with STEMI, and a mutation on MMP-9 rs3918242 may be relevant to susceptibility to MI. 54,55 The ZFP36 family of highly conserved RNA-binding proteins, including ZFP36, ZFP36L1, and ZFP36L2, have been extensively studied in autoimmune diseases. While 28 single-nucleotide polymorphisms (SNPs) in the ZFP36 gene have been reported in patients with autoimmune diseases such as RA, psoriasis, multiple sclerosis (MS), and juvenile idiopathic arthritis (JIA), few studies have investigated the relationship between ZFP36 and SLE.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…53 MMP9 levels were significantly elevated in patients with STEMI, and a mutation on MMP-9 rs3918242 may be relevant to susceptibility to MI. 54,55 The ZFP36 family of highly conserved RNA-binding proteins, including ZFP36, ZFP36L1, and ZFP36L2, have been extensively studied in autoimmune diseases. While 28 single-nucleotide polymorphisms (SNPs) in the ZFP36 gene have been reported in patients with autoimmune diseases such as RA, psoriasis, multiple sclerosis (MS), and juvenile idiopathic arthritis (JIA), few studies have investigated the relationship between ZFP36 and SLE.…”
Section: Discussionmentioning
confidence: 99%
“…53 MMP9 levels were significantly elevated in patients with STEMI, and a mutation on MMP-9 rs3918242 may be relevant to susceptibility to MI. 54,55…”
Section: Discussionmentioning
confidence: 99%
“…In patients without a metabolic syndrome, neither the T-allele occurrence nor MMP-9 activity were associated with the risk of an event [ 67 ]. The meta-analysis of literature concerning the association of MMP-9 rs3918242 SNP and susceptibility to MI revealed that carriers of CT and TT genotypes were less susceptible to MI in comparison with CC homozygotes [ 68 ]. As regards MMP-12 A/G polymorphism, carriers of G allele, which were characterized by lower MMP-12 promoter activity (-82AG and GG genotypes), had an increased risk of having MI and two or three vessel disease [ 56 , 69 ].…”
Section: Role Of Mmps In Cardioembolic Strokementioning
confidence: 99%
“…A substantial body of knowledge related to its biological underpinnings has been accumulated. The intricate interplay of genetic predispositions, lipid profiles, inflammatory markers, hemodynamic factors, and the decline of sex hormones have been previously discussed [5][6][7][8]. Cardiovascular risk factors such as high blood pressure and dyslipidemia, among others, are considered in the development of myocardial infarction [5,6].…”
Section: Introductionmentioning
confidence: 99%
“…The intricate interplay of genetic predispositions, lipid profiles, inflammatory markers, hemodynamic factors, and the decline of sex hormones have been previously discussed [5][6][7][8]. Cardiovascular risk factors such as high blood pressure and dyslipidemia, among others, are considered in the development of myocardial infarction [5,6]. Age is an independent nonmodifiable cardiovascular risk factor that may be compounded by other additional modifiable factors, including frailty and diabetes, which are known to complicate and enhance cardiovascular risk factors associated with the onset of advanced age [6].…”
Section: Introductionmentioning
confidence: 99%